Implementation of Preventive Physical Exercises to Reduce Knee and Wrist Injuries in Volleyball Athletes - Jamaluddin, Jamaluddin; Ridwan, Andi (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Knee and wrist injuries are two common problems experienced by volleyball athletes, primarily due to jumping, landing, and repetitive upper extremity movements. This study aims to assess the effectiveness of implementing a preventive physical training program in reducing the frequency and risk of knee and wrist injuries in volleyball athletes at the BKMF FIKK UNM. The study used a quantitative approach with a pretest-posttest control group design. The sample consisted of 30 active athletes who had been participating in training for at least 3 months. The intervention was administered for 8 weeks, three times per week, and included core stabilization exercises, knee and wrist muscle strengthening, proprioception, and landing technique. Data were collected through injury questionnaires, handgrip strength tests, single-leg balance tests, and observations of landing technique. The results showed a reduction in the frequency of knee injuries from 60% to 30%, and wrist injuries from 43% to 20%. Wrist strength increased from 28.7 kg to 32.5 kg, and leg balance time increased from 21.3 seconds to 26.4 seconds. A paired-sample t-test showed significant results (p < 0.05), and an effect size (Cohen's d) value > 0.8 indicated a large effect. In conclusion, the preventive physical training program has been shown to be statistically and practically effective in reducing injuries and improving physical performance. This intervention is recommended for continued implementation in collegiate athletic training environments.